KEDUDUKAN ANAK PEREMPUAN DALAM PEMBAGIAN HARTA WARISAN MENURUT HUKUM WARIS ISLAM DAN HUKUM WARIS ADAT (Studi Penelitian di Desa Pasir Kecamatan Tripe Jaya Kabupaten Gayo Lues Provinsi Aceh) - Saprun, Muhammad; Jumadiah, Jumadiah; Afrizal, T. Yudi (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2023)
The inheritance system according to Islamic law has been explained in the Qur'an. the happiness of two daughters". (Q.S. An-Nisa: 11) While the inheritance system according to customary law is influenced by the hereditary system used in customary law communities, in Indonesia customary law varies depending on social and cultural life. Inheritance in the Gayo tribe adheres to the Patrilineal system, namely the system of descent drawn according to the father's line, where the male position is more prominent than the female. This research aims to determine the position of daughters in the distribution of inheritance according to Islamic law and the customary law of the Gayo Lues tribe, and to determine the legal basis and its comparison with the position of daughters as heirs. This research method is a qualitative and empirical juridical approach, descriptive in nature, and the data sources used are respondents and informants, data collection techniques used are through field research and library research. Based on the research results, it shows that the position of daughters regarding inheritance according to Islamic law is the same, meaning that they both receive inheritance, but what is different is the amount of property that each of them receives. Meanwhile, according to Gayo customary law, the position of men is more prominent than the position of women, women will not inherit property if their marriage is through a juelen marriage, the only thing that exists is a gift from their parents, not in the name of inheritance. The legal basis for women as heirs is the Al-Qur'an surah An-Nisa verse 11 which means, "The share of a son is equal to two shares of a daughter." It is recommended for Gayo tribal leaders and the government to revise the customary law that has been adopted by the Gayo community, especially inheritance issues, so that they follow religious law in accordance with what has been explained in the Koran so that Gayo tribal girls receive inheritance. Keywords: ( Inherittance, Distribution of inheritance, Womens ringts)